New citizens for a new society : the institutional origins of mass schooling in Sweden - Boli, John, 1948- (Comparative and international education series ;, 1989)
Employing a macro-sociological perspective applicable to all Western countries, this book argues that mass schooling is an essentially ideological enterprise. Concentrating on the 1650-1850 period in Swedish history, the book traces the institutionalization of the universal, egalitarian individual and the homogeneous, integrated national polity as primordial social elements in place of the corporate groups of estate society. It then studies the reorganization of the Swedish polity as a secular project for the pursuit of progress under the direction of an active bureaucractic state. These transformations led to the ideology of mass schooling as a ceremonial means of preparing competent, responsible citizens who could participate successfully in the rationalized, exchange-oriented polity. The book's detailed study of primary schooling between 1800 and 1880 supports this theory, demonstrating that competing theories - functionalist, social control, status competition, and modernization arguments - are contradicted by the Swedish primary schooling in the 20th century and speculates about future mass schooling developments.